Oral Complications in Adult Patients Under Chemotherapy Treatment - Wafaa M. A.; Rajaa H. A.; Sajid M. H. (College of Pharmacy / Mustansiriyah University, 2011)
Aim of the study to assess oral complications under chemotherapy treatment (still from protocol therapy till end it) 125 patients (80 males and 45 females) admitted to blood diseases and oncology unit in Baghdad teaching hospital and bone marrow transplantation center from 25th April 2010 to the 25th June 2010. Age from 18 years and above to start protocol therapy all patients were diagnosed by physician as oncology's patients, questionnaires use in the study are consist of 3 part (1st part: demographic characteristics, 2nd part clinical characteristics, 3rd part main oral complications. Data analyzed were by use frequency, percentage and mean of score. Study show the younger stage, malesand student, secondary school graduate, diagnosed by Dr, as leukemia, short time duration of disease and also duration in hospitalization, oral complications were present in pain and mucosits, redness, thick stringer saliva, mouth bleeding, change in taste, dry mouth and burning sensation